2016
DOI: 10.1152/ajpendo.00194.2016
|View full text |Cite|
|
Sign up to set email alerts
|

Connective tissue growth factor is critical for proper β-cell function and pregnancy-induced β-cell hyperplasia in adult mice

Abstract: During pregnancy, maternal β-cells undergo compensatory changes, including increased β-cell mass and enhanced glucose-stimulated insulin secretion. Failure of these adaptations to occur results in gestational diabetes mellitus. The secreted protein connective tissue growth factor (CTGF) is critical for normal β-cell development and promotes regeneration after partial β-cell ablation. During embryogenesis, CTGF is expressed in pancreatic ducts, vasculature, and β-cells. In adult pancreas, CTGF is expressed only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Other mice were time-mated with male C57BL/6 mice. The pregnant mice were sacrificed at G16, the peak of beta-cell proliferation as reported by us14 and by others5–10 (figure 3A). At G16, we detected red fluorescent cells only in beta cells (about 80% of beta cells were red) from the mice that had received either AAV–RIP–shPlGF or AAV–RIP–scrambled, suggesting that these viruses only transduced beta cells, which again confirmed the specificity of the RIP in the viral structure (figure 3B–C).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Other mice were time-mated with male C57BL/6 mice. The pregnant mice were sacrificed at G16, the peak of beta-cell proliferation as reported by us14 and by others5–10 (figure 3A). At G16, we detected red fluorescent cells only in beta cells (about 80% of beta cells were red) from the mice that had received either AAV–RIP–shPlGF or AAV–RIP–scrambled, suggesting that these viruses only transduced beta cells, which again confirmed the specificity of the RIP in the viral structure (figure 3B–C).…”
Section: Resultsmentioning
confidence: 96%
“…Studies on pregnant women and rodents have suggested that the gestational increases in insulin production and secretion by beta cells may be largely attributable to beta-cell growth during this period 5–10. Indeed, numerous studies have shown that gestational increase in beta-cell mass primarily stems from beta-cell proliferation 11–14.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enhanced β‐cell proliferation in this model occurs through CTGF upregulation of ERK/MAPK‐dependent TGFβ signaling and other growth factors . CTGF is also required for pregnancy‐induced β‐cell hyperplasia and for normal β‐cell function . The role of CTGF in human β‐cell function and β‐cell mass regulation is unknown.…”
Section: Pancreatic Islet Microenvironmentmentioning
confidence: 99%
“…Other islet endothelial-derived factors can also modulate beta cell expansion. Haploinsufficiency of Ctgf (the gene encoding connective tissue growth factor [CTGF]) resulted in decreased beta cell proliferation during pregnancy [14], while genetic deletion of the anti-angiogenic factor thrombospondin-1 (THBS1), results in islet hyperplasia in young adult mice [15]. Despite the opposing effects of CTGF vs THBS1 deficiency on beta cell regeneration, both molecules exert positive effects on beta cell function.…”
Section: The Role Of Islet Endothelial Cells In Supporting Adult Betamentioning
confidence: 99%